ANALYSIS OF AMERICAN SLANG IN MOVIE “LAUGH OF LOUD” - Tiarma Ika Yuliana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
Slang is an important feature in American culture. It is more effective than standard or conventional English , so the writer is interested to discuss and classify of slang words in Laugh of Loud movie. The purpose of this research is to classify slang word in Laugh of Loud (LOL) movie based on the characteristic on Andersson and Trudgill theory. This research used the descriptive qualitative method. The data source of this research is taken from the movie script of Laugh of Loud (LOL) directed by Lisa Azuelos, Karim Ainouz and Nans Delgado with the main the data is American slang. Based on the research result, there are 35 slang words or phrases in the movie of LOL, the slang is divided into four categories: (1) 8 slang words or phrases as the neutral syntactic level, (2) 10 slang words or phrases as typical informal situations, (3) 2 slang words or phrases as typical of spoken language, and (4) 15 slang words or phrases as creative. The meaning of slang words or phrases as informal situation category can be found in a dictionary.Key words: American slang, phrases , movie